A Systematic Review of Intangible Cultural Heritage from the Perspective of Cultural Ecology - Lijuan, Ai; Pintong , Sarawuth (Journal of Arts and Thai Studies, 2024)
Objectives: This review aims to provide a theoretical framework and strategic support for the safeguarding of intangible cultural heritage (ICH) from a cultural ecology perspective by analyzing the research methodologies, aspects, and findings in the published literature. Methods: With reference to the methodology and structure of a systematic literature review, this review of 47 representative papers was conducted by screening the relevant literature in Chinese and English published in the last 12 years. Results: As a methodology, these articles either built the theoretical framework and methodology on an ecological method or a previous method of cultural ecology. Regarding research aspects, static and dynamic aspects were used to study the results of factor interaction and cultural diffusion, respectively. In terms of research conclusions, numerous empirical and case studies were conducted to promote the sustainable development of ICH for regional society, economy, and culture. Future scholarly research could focus more on clarifying terminological norms, integrating interdisciplinary approaches, and assessing the feasibility and sustainability effects of the findings. Application of this study: The study contributes insight into the methods of maintaining the authenticity and living heritage of its cultural genes from a new perspective, which is conducive to the search for a balanced scale between tradition and innovation, inheritance, and revitalization of ICH. Meanwhile, the study is beneficial to provide theoretical and practical references for communities and localities in ICH safeguarding and resource activation.